2013
DOI: 10.3109/14767058.2013.784251
|View full text |Cite
|
Sign up to set email alerts
|

Expression of P-selectin (CD62P) on platelets after thrombin and ADP in hypotrophic and healthy, full-term newborns

Abstract: Hypotrophic newborns are capable of greater platelet activation in comparison with healthy term newborns. However, gender does not affect the expression of P-selectin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Wasiluk et al 55 reported that the thrombopoietin level in SGA newborns is higher than that in healthy term newborns and is positively correlated with the severity of the SGA, although no association could be found in the SGA group between platelet count and TPO. In another study by Wasiluk et al, 56 4.21% of the platelets of IUGR neonates expressed P-selectin (CD62P), a marker of platelet stimulation, versus 2.88% of the AGA control group. After the addition of platelet activators such as thrombin and ADP, there was a statistically significant increase in platelet activation in IUGR infants compared with AGA.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Wasiluk et al 55 reported that the thrombopoietin level in SGA newborns is higher than that in healthy term newborns and is positively correlated with the severity of the SGA, although no association could be found in the SGA group between platelet count and TPO. In another study by Wasiluk et al, 56 4.21% of the platelets of IUGR neonates expressed P-selectin (CD62P), a marker of platelet stimulation, versus 2.88% of the AGA control group. After the addition of platelet activators such as thrombin and ADP, there was a statistically significant increase in platelet activation in IUGR infants compared with AGA.…”
Section: Resultsmentioning
confidence: 95%
“…80 In addition, the incidence of DIC and neonatal thrombosis and stroke is increased in FGR neonates. 7 16 18 20 21 27 Besides incidences of neonatal DIC and thrombosis, which are known causes of increased platelet consumption and destruction, intraplacental platelet consumption and thrombi formation is presumed as another possible mechanism for thrombocytopenia, as supported by Wasiluk et al 55 56 In pregnancies complicated by FGR placental insufficiency is caused by anomalous villous vessels, endothelial dysfunction, leading to placental vasoconstriction, platelet activation, and high UA-PI. As a result, a microangiopathic condition is triggered, causing platelet consumption and eventually a small placenta.…”
Section: Discussionmentioning
confidence: 99%
“…The hemostatic profile of IUGR neonates is an area of wide interest, as they experience hemorrhagic, as well as thrombotic complications during the neonatal period, such as pulmonary and gastrointestinal hemorrhage, hemorrhagic neonatal stroke, and disseminated intravascular coagulopathy (DIC) [7][8][9][10][11][12][13][14]. In IUGR pregnancies, placental insufficiency is the result of thrombi formation, defective endothelium, intraplacental platelet activation, and consumption, leading to small placentas and neonatal thrombocytopenia [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…However, whether the process could result in platelet activation damage is a question that has caused widespread concern and remains unanswered. Laboratory indicators for evaluating the activation of platelets include β-TG, GPIb (CD42), the platelet aggregation test or GPIIb/IIIa (CD41), soluble P-selectin, platelet surface P-selectin (CD62) (Wasiluk et al, 2013), among which CD62 is the best. Thus, we detected and analyzed the platelet P-selectin (CD62P) surface expression of apheresis platelets with different retention periods using flow cytometry before and after leukocyte filtration to evaluate the effects of leukocyte filtration on platelet activation.…”
Section: Introductionmentioning
confidence: 99%